SET and RESET Kinetics of SrTiO3-based Resistive Memory Devices. Issue 1790 (2015) - Fleck, Karsten; Böttger, Ulrich; Waser, Rainer; Menzel, Stephan
ABSTRACT: In this paper we present a study of the switching kinetics of SrTiO3 based resistive switching memory devices. A pulse scheme is used to cycle the cells between the high resistive state (HRS) and the low resistive state (LRS) thereby monitoring the transient currents for a precise analysis of the SET and RESET transitions. By variation of the width and amplitude of the applied pulses the switching kinetics are studied between 10 -8 and 10 4 s. Taking the pre-switching currents into account, a power dependency of the SET is found that emphasizes the importance of local Joule heating for the nonlinearity of the switching kinetics.